Efektivitas Dewan Masyayikh Sebagai Penjamin Mutu Pendidikan Pesantren Berdasarkan Undang-Undang Nomor 18 Tahun 2019 dalam Deradikalisasi Agama di Pesantren - Muhamad Rizaldi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
This research aims to see the effectiveness of the masyayikh council as a guarantor of the quality of Islamic boarding school education based on Law Number 18 of 2019 in deradicalizing religion in Islamic boarding schools. As a quality guarantor who is expected to maintain the characteristics, traditions, independence and diversity of Islamic boarding schools, the masyayikh council has the authority to determine the curriculum of teaching materials for students and has the power to regulate religious deradicalization. This research is based on normative research (legal research) and relies on literature reviews. The results of this research show that the Masyayikh Council as a quality guarantor substantially has the authority to carry out religious deradicalization, then in terms of the legal structure the Ministry of Religion as the implementer has attempted to carry out the mandate of the law. However, culturally there is no certainty of implementation from the community council in society.